BS EN IEC 62271-201. High-voltage switchgear and controlgear. Part 201. AC solid-insulation enclosed switchgear and controlgear for rated voltages above 1 kV and up to and including 52 kV (7th June 2023) - British Standards Institution,
No abstract available